2017
DOI: 10.1371/journal.pone.0189778
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-containing hydrogels as an intraocular lens for sustained drug release

Abstract: To improve the efficacy of anti-inflammatory factors in patients who undergo cataract surgery, poly(2-hydroxyethyl methacrylate-co-methyl methacrylate) (p(HEMA-co-MMA)) hydrogels containing β-cyclodextrin (β-CD) (pHEMA/MMA/β-CD) were designed and prepared as intraocular lens (IOLs) biomaterials that could be loaded with and achieve the sustained release of dexamethasone. A series of pHEMA/MMA/β-CD copolymers containing different ratios of β-CD (range, 2.77 to 10.24 wt.%) were obtained using thermal polymerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 58 publications
(50 reference statements)
4
14
0
Order By: Relevance
“…By contrast, γ-CDHSA2 and γ-CDHSA3 were higher, 450% and 600%, respectively, as depicted in Figure 9 . As has been described in other works [ 50 , 51 ], the swelling index depends on the nature of the polymer, the average molecular weight, the degree of crosslinking, the rigidity of the polymer chain and the network mesh size as well as external conditions, such as pH and temperature [ 50 , 51 ], Moreover, the swelling index observed could be related with the absorption mechanism, which is determined by the diffusion process of water into the pores of hydrogel [ 52 ].…”
Section: Resultsmentioning
confidence: 53%
“…By contrast, γ-CDHSA2 and γ-CDHSA3 were higher, 450% and 600%, respectively, as depicted in Figure 9 . As has been described in other works [ 50 , 51 ], the swelling index depends on the nature of the polymer, the average molecular weight, the degree of crosslinking, the rigidity of the polymer chain and the network mesh size as well as external conditions, such as pH and temperature [ 50 , 51 ], Moreover, the swelling index observed could be related with the absorption mechanism, which is determined by the diffusion process of water into the pores of hydrogel [ 52 ].…”
Section: Resultsmentioning
confidence: 53%
“…The presence of HPBCD decreased the wettability of the material. This is an interesting result as in the past it has been reported that the presence of cyclodextrins in hydrogels improves the wettability (reduces contact angle) of the materials (35,36). This can be explained by looking at the structure of the surface.…”
Section: Hydrogel Synthesis and Characterisationsupporting
confidence: 57%
“…This figure shows that the swelling index increased significantly with time for the set of γ-CDPVAHMAs and at both pH models. As has been reported in previous works, the swelling degree has a direct relationship with the structural nature of the polymer and its properties, including the average molecular weight, the rigidity of the polymer chain, the degree of crosslinking, network mesh size and external conditions, such as temperature and pH [13,45]. Furthermore, the swelling degree observed could depend on the absorption mechanism, which is determined by the diffusion process of water into the pores of hydrogel [46].…”
Section: Resultsmentioning
confidence: 88%